A synchronous filter for gear vibration monitoring using computational intelligence - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2013)
Dissertation (M Eng (Mechanical and Aeronautical Engineering))--University of Pretoria, 2006.